Myanmar household welfare survey round two: Note on sample characteristics and weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
The second round of the MHWS was carried out between April 7th, 2022, and June 24th, 2022. In the second round, 12,142 households responded to the survey, 7,786 households were interviewed in both the first and second round, 4,356 households were added in the second round, while 4,314 households dropped out of the sample after the first round. Issues with blackouts and ongoing conflict made it difficult to collect data from rural lower-educated households. After weighting, the sample is not statistically different from the round one sample, in terms of household location, percent farming households, and percent lower-educated households.